Developing national standards for the accreditation of undergraduate medical education and training in South Africa - Hannemarie Bezuidenhout; Kerneels Nel; Marietjie Nel (Acta Academica, 2004)
In this study, quality assurance and accreditation in higher education were investigated, and standards for the self-evaluation of medical schools and the accreditation of medical education in South Africa were identified. A literature study formed the basis for the investigation, while the Delphi technique was used for the empirical study. A set of 110 standards was compiled, comprising both absolute standards and standards aimed at encouraging development. The standards are suitable for verifying the quality of education, for use as a lever for change and reform and for reference as principles guiding quality assurance. This study will facilitate the attainment of the dual goal of the accreditation process, namely to guarantee the quality of educational offerings to all users and concerned bodies, and to promote the enhancement of academic standards.